Elf [videorecording (DVD)] - Favreau, Jon; Ferrell, Will, 1967-; Caan, James; Deschanel, Zooey, 1980-; Steenburgen, Mary; Tay, Daniel, 1991-; Asner, Edward; Newhart, Bob; Love, Faizon; Dinklage, Peter; Sedaris, Amy (New Line Home Entertainment, 2004)
A human baby accidentaly ends up at the North Pole and grows up among the elf community. Buddy, as he comes to be known, knows that he's "special". When he's 30, Buddy learns from Santa that he's really a human. He decides to go in search of his father, to find out where he belongs. He walks to Manhattan, and is immediately run over by a cab. His father at first rejects him and Buddy ends up in a department store where other elves are working. But all the while, things are looking bad for Santa Claus. When Santa crashes his sleigh in Central Park, it's Buddy's moment to shine.